2008
DOI: 10.1038/labinvest.2008.29
|View full text |Cite
|
Sign up to set email alerts
|

Developmental reprogramming of IGF signaling and susceptibility to endometrial hyperplasia in the rat

Abstract: In rodents, a brief neonatal exposure of the developing reproductive tract to the xenoestrogen, diethylstilbestrol (DES) reprograms developing tissues to increase susceptibility to tumorigenesis in adult animals, including uterine adenocarcinoma. Progression from a normal endometrium to carcinoma occurs via the intermediate stage of endometrial hyperplasia. We previously reported that endometrial hyperplasia in postmenopausal women is linked to abnormal insulin-like growth factor-I (IGF-I) signaling. To identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…IRS1 is an upstream component of the MAPK/ERK and the IGF-1 signaling pathways and is associated with a susceptibility to insulin resistance. Global activation of IGF-IR signaling and loss of negative feedback to IRS-1 appear to be reprogrammed in endometrial hyperplasia (18). IGF1R is overexpressed in the majority of malignant tissues, where it binds IGF to function as an anti-apoptotic agent by enhancing cell survival (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…IRS1 is an upstream component of the MAPK/ERK and the IGF-1 signaling pathways and is associated with a susceptibility to insulin resistance. Global activation of IGF-IR signaling and loss of negative feedback to IRS-1 appear to be reprogrammed in endometrial hyperplasia (18). IGF1R is overexpressed in the majority of malignant tissues, where it binds IGF to function as an anti-apoptotic agent by enhancing cell survival (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In each field, 100 epithelial cells were selected and viewed. The PCNA and Ki-67 indexes were expressed as percent of positive cells [10,11].…”
Section: Immunhistochemical Evaluationmentioning
confidence: 99%
“…Several groups have also investigated the role of small-molecule mTOR kinase inhibitors in endometrial cancer cell lines (59,63) and the effects of mTOR inhibitors on mouse models of endometrial cancer (3,(64)(65)(66).…”
Section: Preclinical Studies Of Mtor Inhibition In Endometrial Cancersmentioning
confidence: 99%
“…Mirroring human studies, tissue culture studies have shown contradictory results with regard to the impact of PTEN status on rapamycin sensitivity (32,40,41,43). Investigators have also examined rapalog treatment in mouse models of endometrial hyperplasia, and they found that treatment with rapalogs reduced tumor burden, slowed progression of disease, and decreased the incidence of hyperplastic lesions in mice predisposed to hyperplasia (3,(64)(65)(66).…”
Section: Preclinical Studies Of Mtor Inhibition In Endometrial Cancersmentioning
confidence: 99%